A Review on Nanocarrier Mediated Treatment and Management of Triple Negative Breast Cancer: A Saudi Arabian Scenario - Nahvi, Insha; Belkahla, Sana; Biswas, Supratim; Chakraborty, Suparna (Frontiers in Oncology, 2022)
Human beings continue to be petrified by the devastating effects of cancer for decades and thus a pursuit for the development of anticancer agents sees ever increasing trend in the past few decades. Globally, breast cancer is the most common malignancy in women as well as the second most common cause of cancer-related deaths. In Saudi Arabia breast cancer is the most common type of cancer among women constituting almost 14.2 % of the total cancer burden. Triple-negative breast cancer (TNBC) is a subtype of breast cancer which is a pathologically diverse disease of higher grade characterized by the absence of the estrogen receptor (ER), the progesterone receptor (PR), and the human epidermal growth factor receptor 2 (HER2) expressions. Inspite of the considerable advancements achieved in the therapeutic management of cancer, still TNBC remains an unbeatable challenge which requires immediate attention as it lacks conventional targets for treatment, which leads to poor clinical prognosis. The present research goals are directed towards development and implementation of treatment regimens with enhanced bioavailability, targetability, minimized systemic toxicity and improved outcome of treatment options. The present treatment and management scenario of TNBC continues to provoke the oncologist as well as the Nano-medical scientist to develop novel and efficient Nano therapies. Lately, scientific endeavors addressed the importance of enhanced availability, targeted cellular uptake with minimal toxicity, which are achieved by the application of Nano drug-carriers. The present review intends to summarize the incidence rates of TNBC patients, importance of nanotherapeutic options for patients suffering from TNBC, identification of promising molecular targets, challenges associated with the development of targeted nanotherapeutics with special reference to the Saudi Arabian context.